Pretoria Student Law Review 2016 - 10 - Cara Furniss (Pretoria University Law Press (PULP), 2016)
It is with great joy that I, along with the editorial committee, present to you, reader, the 2016 Pretoria Student Law Review. I believe it is only fitting that the tenth edition is one that portrays, very clearly, a new chapter in the life of this student publication. This year has not only been a challenging one for students, staff and parents but also for the citizens of South Africa as a whole. It is thus with even greater pleasure that we offer our humble contribution to legal academia. As the editorial board we are extremely proud of successfully completing this most important tenth edition in such tumultuous times. Many challenges have both been overcome and discovered in this year$1 (Bs exciting journey of creating this publication. Every year experiences different authors with varied contributions and themes but this tenth edition is one which illustrates a certain gusto and determination on the part of those who worked towards its completion. With that said, I would like to thank the authors for their submissions and tireless effort to meet (often exceedingly pressed) deadlines. My thanks also goes to the artist for this edition, Marijke Benade and Lizette Hermann for her support during this particularly unique time; Prof Anton Kok & Prof Andre Boraine, for their support in various ways and on short notice. But of course, thank you to the editorial team of 2016. Abel Maluleka, Abrie van der Merwe, Carin Cross, Daniel Badenhorst, Larisse Prinsen and Roxanne Gilbert; without your willingness to assist, there would be nothing between these pages. Thank you to Sarah Burford, in particular, who is not only part of the editorial team but who greatly assisted me with concluding edits and proofreading. This year$1 (Bs edition includes a diverse range of articles. Some are close to home while others grapple with issues abroad. From feminism & queer theory, to child rights, sports law, free higher education, and of course, the language debate, our authors have ensured that every reader will find something to both challenge and broaden their minds. I do hope that you enjoy this precious bundle of what the students at the Faculty of Law, University of Pretoria, have to offer. Editor in chief: Cara Furniss Editors: Daniel Badenhorst, Sarah Burford, Carin Cross, Roxanne Gilbert, Abel Maluleka, Larisse Prinsen & Abrie van der Merwes
English
Keywords: law journals Pretoria Student